GIS Mapping of Implemented Technologies across Different Agro-Ecologies and Demographic Settings to Help Evaluation of Adoption Practices - Association Malienne d'éveil au Développement Durable (International Food Policy Research Institute, 2023)
Technology adoption by farmers is linked to changes in environmental and climate variations but also to the household socio economic status and the cultural acceptance of technologies. The reliability and replicability of the technologies depend to the specific context where technologies are developed and implemented. Regarding the available technologies developed in phase I of the Africa RISING project and technologies under validation in phase II it is important to map and characterize using GIS and remote sensing technologies under different agro-ecological and socio-economic context.